Brain Knowledge and the Prevalence of Neuromyths among Prospective Teachers in Greece - Papadatou-Pastou, Marietta; Haliou, Eleni; Vlachos, Filippos (Frontiers in Psychology, 2017)
Although very often teachers show a great interest in introducing findings from the field of neuroscience in their classrooms, there is there is growing concern about the lack of academic instruction on neuroscience on teachers' curricula because this has led to a proliferation of neuromyths. We surveyed 468 undergraduate (mean age = 19.60 years, SD = 2.29) and 86 postgraduate students (mean age = 28.52 years, SD = 7.16) enrolled in the Departments of Education at the University of Thessaly and the National and Kapodistrian University of Athens. We used a 70-item questionnaire aiming to explore general knowledge on the brain, neuromyths, the participants’ attitude towards neuroeducation as well as their reading habits. Prospective teachers were found to believe that neuroscience knowledge is useful for teachers (90.3% agreement), to be somewhat knowledgeable when it comes to the brain (47.33% of the assertions were answered correctly), but to be less well informed when it comes to neuroscientific issues related to special education (36.86% correct responses). Findings further indicate that general knowledge about the brain was found to be the best safeguard against believing in neuromyths. Based on our results we suggest that prospective teachers can benefit from academic instruction on neuroscience. We propose that such instruction takes place in undergraduate courses of Departments of Education and that emphasis is given in debunking neuromyths, enhancing critical reading skills, and dealing with topics relevant to special education.